Tatalaksana Campak - Vivi Yonanda (Jurnal Medika Hutama, 2022)
Measles is an infection caused by a virus. This disease is self-limiting. Measles is one of the causes of morbidity, especially in infants. Management of measles can be symptomatic or supportive. The purpose of this paper is to determine the management of measles. The method used is literature research by searching for measles, measles, medication, and treatment on Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From a review of the existing literature, the management of measles is fluid administration, symptomatic treatment to treat symptoms, namely the administration of antipyretics, antibiotics in case of secondary infection, and administration of Vitamin A.